Comparative clinical and radiographic results of three fixation systems for transverse subcapital osteotomy in treating hallux valgus - Catá, Ezequiel; Nieto, Ignacio Hernan (Journal of the Foot & Ankle, 2024)
Objective: Compare three fixation models for Bosch osteotomy both clinically and radiographically. Methods: A retrospective comparative study was conducted on patients surgically treated for hallux valgus using Bosch osteotomy with three different fixation systems. The first group was treated with a temporary pin for three weeks; the second, received the same pin plus a screw; and the third, used two screws without a pin. Radiographic analysis included the intermetatarsal angle, metatarsophalangeal angle, percentage of lateral shifting of the metatarsal head, dorsal or plantar migration of the metatarsal head, and consolidation time. Clinical evaluation was performed using the American Orthopaedic Foot and Ankle Society (AOFAS) scale. Complications during follow-up were recorded. Results: Twenty hallux valgus were included in each group. No significant differences were found in radiographic evaluations among groups in the preoperative and final follow-up, except that the third group showed less loss of correction. There were no significant differences in consolidation times. Clinical improvements were observed in all three fixation systems, with no significant differences among them according to the AOFAS scale. Conclusion: No significant clinical or radiographic differences were observed among the three fixation systems, except that the group using two screws showed less loss of correction. Level of evidence IV; Therapeutic studies; Case series.